Mismatch Negativity Affects Muscle Fatigue during Repeated Contraction Trials of Different Durations - Aleksandrov, Aleksander A.; Knyazeva, Veronika M.; Stankevich, Ludmila N.; Dmitrieva, Elena S.; Shestakova, Anna N. (Frontiers in Physiology, 2016)
We examined the effect of involuntary attention switching (related to mismatch negativity generation in the oddball paradigm) on fatigue development during trials of different durations. The experiment consisted of two trials, long (40 minutes) and short (15 minutes), and two experimental conditions in each trial: the simple reaction task (deviants-only paradigm) and the stimuli recognition task (oddball paradigm). In each condition, a participant responded to each target acoustic stimulus by squeezing a handgrip dynamometer. We found the significantly lower rates of fatigue development in the short-trial deviants-only paradigm compared to the long trial. The short- and the long-trial oddball paradigms differed significantly from both the short- and the long-trial deviants-only paradigms. The results demonstrated that the fatigue developed differently depending on the expected trial duration. The involuntary activation of attention broke this subconscious regulative mechanism leading to increase of the compression force during the long trial and its decrease during the short.